Recycling of Polypropylene Recovered from a Composting Plant: Mechanical Behavior of Compounds with Virgin Plastic - Claudio Badini; Oxana Ostrovskaya; Giulia Bernagozzi; Roberta Lanfranco; Stefania Miranda (Recycling, 2023)
The recycling of polypropylene recovered from waste discarded by a composting plant was investigated. The recovery involved a sorting step carried out by means of an optical infrared separator and a subsequent washing treatment. This method of processing allowed us to obtain polypropylene that was only slightly contaminated by other polymeric and inorganic materials. As many tens of tons of polypropylene could be recovered every year in this plant, recycling could be convenient from the economic point of view and beneficial for the protection of the environment. In fact, the landfill of this waste could be reduced in this manner. A possible mechanical recycling route was developed for the recovered plastic. The recycling was carried out by pelletizing the recovered polypropylene, mixing it with a commercial polypropylene feedstock, and manufacturing items by injection molding. In this way, tensile specimens containing different amounts of recycled polypropylene were processed and tested. Their tensile features were compared with those of a commercial polypropylene that was used as a reference. The elastic modulus and tensile strength were slightly worsened when using the recycled plastic, while the strain at failure significantly increased. Nonetheless, the tensile properties of compounds made by mixing recycled and virgin polypropylene were consistent with the characteristics that are expected for polypropylene-based plastics.